DYNAMIC PROJECTION OF CLIMATE CHANGE SCENARIOS ON TROPICAL TREES' ABOVEGROUND CARBON STORAGE IN WEST PAPUA - Sandhi Imam Maulana; Yohannes Wibisono (Indonesian Journal of Forestry Research, 2017)
Through photosynthetic activities, tropical forest ecosystems capture and store the most significant carbon emissions in the form of  biomass compared with other types of  vegetation, and thus play a highly crucial part in dealing with climate change. However, such important role of  tropical forest is very fragile from extreme changes in temperature and precipitation, because carbon storage in forest landscape is strongly related to those climate variables.  This paper examines the impacts of  future climate disturbances on aboveground carbon storage of  three tropical tree species, namely Myristica sp., Palaquium sp., and Syzygium sp. through “what if ” scenarios evaluation using Structural Thinking and Experimental Learning Laboratory with Animation (STELLA). Results highlighted that when the dynamic simulation was running with five IPCC’s climate change scenarios (Constant year 2000 concentrations, B1, A1T, A2, and A1F1) for 200 years simulation period, then moderate climate change scenarios occured, such as B1 and A1T, would have already caused significant statistical deviation to all of  those tree species. At the worst level of  A1F1, the 4°C temperature was coupled with 20% reduction in precipitation. Palaquium sp. showed the highest reduction of  aboveground carbon storage with about 17.216% below its normal value. This finding implies the negative climate feedbacks should be considered  seriously to ensure the accuracy of  long term forest carbon accounting under future climate uncertainty.